2014
DOI: 10.1038/onc.2013.556
|View full text |Cite
|
Sign up to set email alerts
|

ATM-mediated phosphorylation of the chromatin remodeling enzyme BRG1 modulates DNA double-strand break repair

Abstract: ATP-dependent chromatin remodeling complexes such as SWI/SNF (SWItch/Sucrose NonFermentable) have been implicated in DNA double-strand break (DSB) repair and damage responses. However, the regulatory mechanisms that control the function of chromatin remodelers in DNA damage response are largely unknown. Here, we show that ataxia telangiectasia mutated (ATM) mediates the phosphorylation of BRG1, the catalytic ATPase of the SWI/SNF complex that contributes to DSB repair by binding γ-H2AX-containing nucleosomes v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 54 publications
1
55
0
Order By: Relevance
“…A direct role for SWI/SNF in the DDR is also supported by a proteomic screen that identified BRG1, BRM, and other SWI/SNF subunits as targets of ATM and ATR phosphorylation in response to IR or UV treatment [50]. Recently, a direct link between ATM and BRG1 phosphorylation was confirmed [51]. At a functional level, RNAi has been performed to demonstrate that the BAF60A subunit (also known as SMARCD1) is important for γH2AX induction and cell-cycle arrest in response to IR [50].…”
Section: Discussionmentioning
confidence: 98%
“…A direct role for SWI/SNF in the DDR is also supported by a proteomic screen that identified BRG1, BRM, and other SWI/SNF subunits as targets of ATM and ATR phosphorylation in response to IR or UV treatment [50]. Recently, a direct link between ATM and BRG1 phosphorylation was confirmed [51]. At a functional level, RNAi has been performed to demonstrate that the BAF60A subunit (also known as SMARCD1) is important for γH2AX induction and cell-cycle arrest in response to IR [50].…”
Section: Discussionmentioning
confidence: 98%
“…The inhibition of SETD2 ’s phosphorylation by long non-coding RNA HOTAIR has been reported to trigger a reduction of trimethylation on histone H3 thirty-sixth lysine, consequently promoting human liver cancer stem cell malignant growth [41]. SMARCA4 , also known as BRG1 , was shown to modulate DNA double-strand break repair by its phosphorylation [42]. It has been suggested that the enzymatic activity of DNMT1 is possibly modulated by phosphorylation [43], and it has been demonstrated that its phosphorylation by AKT1 kinase increases its stability and abundance [15].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PBAF subunit BAF180 mediates p21 expression in breast tumor cells to suppress tumorigenesis (Xia et al 2008), BRG1 is necessary for efficient RB-mediated cell cycle arrest (Strobeck et al 2000), and BRG1 cooperates with ATM to promote the DNA damage response (Kwon et al 2015). Moreover, mutations in SWI/ SNF subunits and TP53 have a tendency toward mutual exclusivity in multiple cancer types, including breast cancer, suggesting that loss of SWI/SNF function may phenocopy p53 loss to mediate oncogenesis (Kadoch et al 2013).…”
Section: Discussionmentioning
confidence: 99%